The climatologic significance of topography, altitude and region in high mountains – A survey of oceanic-continental differentiations of the Scandes - Löffler, Jörg; Pape, Roland; Wundram, Dirk (ERDKUNDE, 2006)
The heterogeneity of the Norwegian mountain landscape under investigation led to a multi-scale approach. We combined micro-spatial differentiations within small catchments (micro-scale), altitudinal changes of an oceanic and a continental mountain system (meso-scale), and oceanic-continental alteration between these two mountain regions (macro-scale). We analysed differences between micro-climatic site conditions at the spatial scales given above. It was assumed that different superior meteorological phenomena along altitudinal and regional gradients find their expression in local temperature conditions. It turned out that micro-topographic site conditions were superiorly determining thermal changes along altitudinal and oceanic-continental broad-scale gradients. The adiabatic lapse rate did not show high correlations with local temperature gradients. Regional climatic differences between the oceanic western and the continental eastern mountains were significant by means of local and altitudinal temperature gradients. We used isopleth-diagrams of temperature differences and corresponding histograms between each, site–site, low alpine–middle alpine, and oceanic mountain–continental mountain couples to quantify these over-laying phenomena. As a result we quantified the significance of complex differences of temperature gradients across topography, altitude and region in order to enable micro-climate extrapolation and modelling in high mountain landscapes.